An Analysis of the Implementation of the Core Tax Administration System in Enhancing Compliance and Efficiency in Income Tax Reporting at the Education Office of Cimahi City - Aulia Aprilliyanti; Purwanto Purwanto (Universitas Ibn Khladun Bogor, 2026)
The digital transformation of tax administration through the implementation of the Core Tax Administration System (Coretax) has brought significant changes for government institutions acting as withholding tax entities. However, its implementation still faces several challenges, including technical disruptions, a less user-friendly interface, and data inconsistencies between the system and internal documents. This study aims to analyze the implementation of Coretax in improving compliance and efficiency in Income Tax reporting at the Cimahi City Education Office. This research employs a qualitative approach with a case study design using interview, observation, and documentation techniques. The results indicate that the implementation of Coretax has improved tax compliance, particularly formal compliance, as reflected in timely reporting, document completeness, and the integrated execution of taxation procedures. In addition, Coretax has enhanced reporting efficiency through system integration, automated tax calculations, and ease in generating e-Bupot and filing Periodic Tax Returns (SPT Masa). However, technical issues and limited socialization have caused material compliance to remain not fully achieved. The study concludes that Coretax has a positive impact on tax compliance and reporting efficiency, but further system improvements and enhanced user understanding are still needed to optimize its implementation.